2022
DOI: 10.5888/pcd19.210346
|View full text |Cite
|
Sign up to set email alerts
|

State-Specific Prevalence of Inactivity, Self-Rated Health Status, and Severe Joint Pain Among Adults With Arthritis — United States, 2019

Abstract: Arthritis is associated with joint pain, disability, and physical inactivity, potentially resulting in poor quality of life. The Centers for Disease Control and Prevention analyzed 2019 Behavioral Risk Factor Surveillance System data to estimate state-specific arthritis prevalence and, among adults with arthritis, the prevalence of physical inactivity, fair/poor self-rated health status, and severe joint pain. Among adults with arthritis, age-standardized prevalences of physical inactivity, fair/poor health st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Despite the numerous benefits associated with PA, many Americans, including 44% of men and 22% of women with knee osteoarthritis (OA), do not meet the guidelines [ 7 ]. Further, a recent study found that 30% of adults with arthritis report no physical activity in the last 30 days [ 8 ]. Exercise may be particularly beneficial for those with knee OA, as it can improve knee pain and function [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous benefits associated with PA, many Americans, including 44% of men and 22% of women with knee osteoarthritis (OA), do not meet the guidelines [ 7 ]. Further, a recent study found that 30% of adults with arthritis report no physical activity in the last 30 days [ 8 ]. Exercise may be particularly beneficial for those with knee OA, as it can improve knee pain and function [ 9 ].…”
Section: Introductionmentioning
confidence: 99%